Management and Business Development of a Furniture Company in Studio Inside Surabaya - Fahmi, Firjaun Faris; Tambunan, Damelina Basauli (KnE Social Sciences, 2021)
The purpose of this study was to conduct a feasibility analysis to determine the steps in the management and development of furniture businesses in Studio Inside Surabaya. The aspects which were studied were the legal, market and marketing, technical and operational, natural resource and financial aspects. The legal aspect: Interior Business and Custom Furniture Studio Inside have obtained approval from the surrounding community to carry out the company’s activities and the SIUP of the company is in the process of making the deed. The market and marketing aspect: Interior Business and Custom Furniture Studio Inside have been able to maintain the business environment conditions with PEST analysis, maintain the industrial structure with the Five Force Model Porter, analyze STP, and describe the marketing mix. Technical and operational aspects: the Interior Business and Custom Furniture Studio Inside have fulfilled the element of feasibility because of their strategic location and workshop layout that is able to support the company’s activities to the maximum and has established a clear SOP. The human resources aspect: the Interior and Custom Furniture Studio Inside Business has fulfilled the element of eligibility because the organizational structure and position description have been well established. Financial aspects: the Interior Business and Custom Furniture Studio Inside have fulfilled the element of eligibility because the PP, NPV, and PI values have met the conditions under normal and optimistic conditions. Keywords: business feasibility study, interior, furniture